2000
DOI: 10.1074/jbc.275.20.14831
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Threonine, and Not Serine, Function as the Active Site Nucleophile in Proteasomes?

Abstract: Proteasomes belong to the N-terminal nucleophile group of amidases and function through a novel proteolytic mechanism, in which the hydroxyl group of the N-terminal threonines is the catalytic nucleophile. However, it is unclear why threonine has been conserved in all proteasomal active sites, because its replacement by a serine in proteasomes from the archaeon Thermoplasma acidophilum (T1S mutant) does not alter the rates of hydrolysis of Suc-LLVY-amc (Seemü ller, E., Lupas, A., Stock, D., Lowe, J., Huber, R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 60 publications
6
80
1
3
Order By: Relevance
“…In S. cerevisiae, substitutions of Lys 108 (Lys 33 in the mature Pre2p subunit) by Ala or Arg shift about two-thirds of the major processed form toward alternative PacC 27 products shortened at their C termini. This effect is specific for Pre2p, since inactivation of the catalytic Thr residues in Pre3p and Pup1p (accounting for the PGPH and trypsin activities of the proteasome, respectively) have no effect and because substitution of Pre2p N-terminal Thr by Ser, which reduces the ability of the proteasome to degrade proteins (51), also reduces the efficiency of processing to PacC 27 . Involvement of other proteasome subunits in Pre2p K108R shifting of the site of proteolysis to other scissile bonds is likely, because one such abnormal cleavage is impaired by additional inactivation of Pre3p.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, substitutions of Lys 108 (Lys 33 in the mature Pre2p subunit) by Ala or Arg shift about two-thirds of the major processed form toward alternative PacC 27 products shortened at their C termini. This effect is specific for Pre2p, since inactivation of the catalytic Thr residues in Pre3p and Pup1p (accounting for the PGPH and trypsin activities of the proteasome, respectively) have no effect and because substitution of Pre2p N-terminal Thr by Ser, which reduces the ability of the proteasome to degrade proteins (51), also reduces the efficiency of processing to PacC 27 . Involvement of other proteasome subunits in Pre2p K108R shifting of the site of proteolysis to other scissile bonds is likely, because one such abnormal cleavage is impaired by additional inactivation of Pre3p.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, threonine is also found as the catalytic residue in all protease subunits of the proteasome. Although replacement with serine compromises activity, no structural explanation of this surprising effect is apparent (59).…”
Section: Fig 8 Dephosphorylation Of Cdk2 Cak-phosphorylated Wildtymentioning
confidence: 99%
“…This last "postacidic" site had been generally termed postglutamyl peptide hydrolase (PGPH) 1 (6), but we found that it cleaves after aspartates in fluorogenic substrates of caspases and therefore suggested the name "caspase-like" (5). All of these active sites cleave peptide bonds via a nucleophilic attack of the hydroxyl group of the N-terminal threonine of the catalytic ␤-subunit (7)(8)(9). The active subunits are generated from larger precursors that contain a propeptide at their N terminus, which block the active sites until removed autocatalytically during assembly of the 20 S particle (10).…”
mentioning
confidence: 99%